Situation Report: Albania, 24 April 1962 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Chinese Delegation to Albania Albanian Ambassador in North Vietnam Albanian Help to Algerian Youth Australian CC Attacks the Albanian Leaders Albanian Delegation to Rome and Geneva "Zeri i Popullit" on Leninism